The Lived Experiences of Employed Middle-Aged Adults Having Autism Spectrum in Batangas Province - Jervin Dinglasan Quicho; Lykamarie Q. De Ocampo; Kathleen M. De Villa; Audrey E. Evangelista; Dondon R. Ramos (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study explored the lived experiences of the working middle-aged autistic persons, who live in the province of Batangas, Philippines. A qualitative research design was implemented, targeting five respondents aged 35-60 years old, formally diagnosed with Autism Spectrum Disorder, and have 6 months working experience and basic literacy. Purposive and snowball sampling was used. From the data gathered from semi-structured, in-depth interviews, five main themes were developed. These include: (1) Navigating the work place, (2) Social connections and support, (3) Navigating Emotional Terrain in the Workplace, (4) Resilience Drivers in the Workplace, and (5) Growth and self- development. The themes reflected the challenges of participants in their ability to adapt to organizational routines, build interpersonal relationships, and self-regulate emotions as well as the interactions of personal strengths and external support systems that promoted resilience and development. Repeatedly, participants emphasized the importance of support from family members, co-worker and supervisory personnel when dealing with day-to-day problems. Notwithstanding recurring adversities, the participants demonstrated a great sense of pride, belonging and a constant drive to self-development. This study underlined a need for more inclusive and flexible workplaces that were aware of the needs of people with ASD. Creating supportive environments can help neurodiverse employees thrive and reach their full potential.